2011
DOI: 10.1080/13674671003739170
|View full text |Cite
|
Sign up to set email alerts
|

The selective relationship between religious dimensions and social desirability among Polish students

Abstract: This study explores the effect of the position of the religious construct-system (central vs. subordinated vs. marginal) in personality on the relationship between social desirability and structure of religiosity, emotion to God and post-critical belief. The sample comprised Polish Students (N ¼ 200) aged between 19 and 29 years. The Social Desirability Scale, The Structure-of-Religiosity Test and The Post-Critical Belief Scale were employed in the study. The results suggest that religiosity is not associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Public practice correlated positively with assertive behavior (Rydz and Zarzycka 2008). There were no significant correlations between centrality and social desirability (Zarzycka and Rydz 2011). Centrality and all its dimensions correlated positively with civic involvement among middle-aged women.…”
Section: A Review Of the Reserch Involving Polish Crsmentioning
confidence: 65%
“…Public practice correlated positively with assertive behavior (Rydz and Zarzycka 2008). There were no significant correlations between centrality and social desirability (Zarzycka and Rydz 2011). Centrality and all its dimensions correlated positively with civic involvement among middle-aged women.…”
Section: A Review Of the Reserch Involving Polish Crsmentioning
confidence: 65%
“…The processes of de-institutionalization and privatization of religion mean primarily the weakening of bonds with the Church and a de-Christianificatino of religion itself. Zarzycka and Rydz (2011), whose research among Polish students indicated that religiosity is not associated with social desirability.…”
Section: Discussionmentioning
confidence: 99%
“…Latest research indicates that the literal interpretation (external critique and orthodoxy), both among males and females, reduces the sense of coherence (Zarzycka & Tychmanowicz, 2015). No links between the styles of thinking about religion and social desirability have been observed (Zarzycka & Rydz, 2011).…”
Section: The Post-critical Belief Scalementioning
confidence: 99%